Job Satisfaction is Dominant Factor Influencing of Nurse Performance in X Hospital Pekanbaru - Ismainar, Hetty; Djuhaeni, Henny; Magretta, Jeanny Susana (Faculty of Public Health, Universitas Diponegoro, Semarang, Indonesia, 2021)
Introduction: The provision of optimal health services is determined by the quality of health workers. The research objective was to explore the factors that influence the performance of nurses in health service.Method: It was a quantitative analytic study with a cross-sectional design. A total of 58 nurses participated with a purposive random sampling technique. The data was collected by questionnaire and worksheets observation. The statistical analysis was done by Smart PLS (Partial Least Square).Result: This study showed that individual characteristics are correlated to job satisfaction (p-value 0.001) but not correlated with the performance of nurses (p-value 0.468). Organizational factors were correlated to job satisfaction (p-value 0.000) but not correlated to work performance (p-value 0.865). Job satisfaction was correlated to work performance (p-value 0.001). There was a negative correlation between individual characteristics and nurse performance (-0.466). Meanwhile, the organizational factor only has a direct effect of 0.025 on nurse performance. Only job satisfaction has a direct effect on nurse performance with an increase of 0.5 (50%) for every increase of one value of job satisfaction.Conclusion: Job satisfaction is a dominant factor that has a direct effect on nurse performance. Hospital management needs to consider health workforce planning, mapping, and development competency to optimize nurse performance.